2012
DOI: 10.1186/1756-6606-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin reduces CX3CL1 signaling and blocks spinal microglial activation in monoarthritic rats

Abstract: BackgroundSpinal glia, particularly microglia and astrocytes, are of the utmost importance in the development and maintenance of chronic pain. A recent study from our laboratory revealed that gabapentin, a recommended first-line treatment for multiple neuropathic conditions, could also efficiently antagonize thermal hyperalgesia evoked by complete Freund's adjuvant (CFA)-induced monoarthritis (MA). In the present study, we investigated whether the spinal glia are involved in the anti-hyperalgesic effect of gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 51 publications
4
48
0
4
Order By: Relevance
“…We thus further explored the glial localization of CXCL10 in the spinal cord through double immunofluorescence staining. The enlarged area and strength of the immunostaining determined through the image analysis corresponded well with the sites showing activated microglia and astrocytes after injury [17,18]. As previously described, spinal glial activation can be determined by measuring Iba-1 (microglia) and GFAP (astrocytes) immunoreactivity [14].…”
Section: Discussionsupporting
confidence: 61%
“…We thus further explored the glial localization of CXCL10 in the spinal cord through double immunofluorescence staining. The enlarged area and strength of the immunostaining determined through the image analysis corresponded well with the sites showing activated microglia and astrocytes after injury [17,18]. As previously described, spinal glial activation can be determined by measuring Iba-1 (microglia) and GFAP (astrocytes) immunoreactivity [14].…”
Section: Discussionsupporting
confidence: 61%
“…A role for neuronal FKN in microglia activation has also been demonstrated in models of acute peripheral inflammation. In a rat monoarthritis model, intra-articular injection of CFA produced robust microglia activation and increased expression of neuronal FKN in the spinal cord [48]. Here, the use of CX3CR1-GFP reporter mice confirmed that the FKN receptor was expressed primarily on microglia.…”
Section: Discussionmentioning
confidence: 58%
“…At this time microglial cells are also seen to proliferate [46]. Inflammation in peripheral tissues is also accompanied by microgliosis that can occur acutely after intraplantar or intra-articular injection of complete Freund’s adjuvant (CFA), which results in pain-related behavioral hypersensitivity and microgliosis within hours [47, 48]. Only recently have researchers started to explore microglial activation associated with experimental OA, using the MIA model.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin reduces chemokine (C-X3-C motif) ligand 1 (CX3CL1) signaling and blocks spinal microglial activation in monoarthritic rats [146]. On the other hand, despite the fact that microglia are involved in the development of allodynia in the mouse spinal nerve ligation model, gabapentin inhibites the development of allodynia without suppression of microglial activation [147].…”
Section: Other Antiepileptics and Microgliamentioning
confidence: 99%